Diversity and Functional Properties of Lactic Acid Bacteria Isolated From Wild Fruits and Flowers Present in Northern Argentina - Ruiz Rodríguez, Luciana G.; Mohamed, Florencia; Bleckwedel, Juliana; Medina, Roxana; De Vuyst, Luc; Hebert, Elvira M.; Mozzi, Fernanda (Frontiers in Microbiology, 2019)
Lactic acid bacteria (LAB) are capable of converting carbohydrate substrates into organic acids (mainly lactic acid) and producing a wide range of metabolites. Due to their interesting beneficial properties, LAB are widely used as starter cultures, as probiotics, and as microbial cell factories. Exploring LAB present in unknown niches may lead to the isolation of unique species or strains with relevant technological properties. Autochthonous rather than allochthonous starter cultures are preferred in the current industry of fermented food products, due to better adaptation and performance of autochthonous strains to the matrix they originate from. In this work, the lactic microbiota of eight different wild tropical types of fruits and four types of flowers were studied. The ability of the isolated strains to produce metabolites of interest to the food industry was evaluated. The presence of 21 species belonging to the genera Enterococcus, Fructobacillus, Lactobacillus, Lactococcus, Leuconostoc, and Weissella was evidenced by using culture-dependent techniques. The isolated LAB corresponded to 95 genotypically differentiated strains by applying rep-PCR and sequencing of the 16S rRNA gene; subsequently, representative strains of the different isolated species were studied for technological properties, such as fast growth rate and acidifying capacity; pectinolytic and cinnamoyl esterase activities, and absence of biogenic amine biosynthesis. Additionally, the strains´ capacity to produce ethyl esters as well as mannitol was evaluated. The isolated fruit- and flower-origin LAB displayed functional properties that validate their potential use in the manufacture of fermented fruit-based products setting the background for the design of novel functional foods.